Evaluation of crystallization kinetics of poly (ether-ketone-ketone) and poly (ether-ether-ketone) by DSC - Vasconcelos, Gibran Da Cunha (2010)
The poly (aryl ether ketones) are used as matrices in advanced composites with high performance due to its high thermal stability, excellent environmental performance and superior mechanical properties. Most of the physical, mechanical and thermodynamic properties of semi-crystalline polymers depend on the degree of crystallinity and morphology of the crystalline regions. Thus, a study on the crystallization process promotes a good prediction of how the manufacturing parameters affect the developed structure, and the properties of the final product. The objective of this work was to evaluate the thermoplastics polymers PEKK e PEEK by DSC, aiming to obtain the relationship between kinetics, content, nucleation and geometry of the crystalline phases, according to the parameters of the Avrami and Kissinger models. The analysis of the Avrami exponents obtained for the studied polymers indicates that both showed the formation of crystalline phases with heterogeneous nucleation and growth geometry of the type sticks or discs, depending on the cooling conditions. It was also found that the PEEK has a higher crystallinity than PEKK.